Comparing the sensitivities of measures of adherence to antihypertensive drugs using korean national health insurance claims data - Choo, Eunjung; Jung, Minji; Shin, Jaekyu; Lee, Sukhyang (Patient Preference and Adherence, 2021)
Purpose: Numerous studies have utilized various forms of adherence measures. However, methods for measuring adherence are inconsistent. Moreover, few studies are available that have compared sensitivities of the effects of several criteria on medication adherence. This study aims to compare measures of adherence using varied analytical decisions. Materials and Methods: We included three measures for adherence: proportion of days covered with one or more medications (PDCwith≥1), duration weighted mean PDC (PDCwm), and daily polypharmacy possession ratio (DPPR). We compared the sensitivities of the measures by changing parameters in the Korean nationwide claims database. First, we used PDCwith≥1 as our base model. Then, we divided an adherence measure algorithm into three categories: (1) definition of data cleaning, (2) inclusion criteria and observation period, and (3) calculation methods of medication adherence. The categories included eight decision nodes that incorporated 25 alternative options. Finally, we assessed the medication adherence for the base-case with commonly used values and then varied to measure with each alternative option. Results: The base-case included 14,288 beneficiaries with antihypertensives. Among eight decisions, both handling an end-date-of-study and overlaps had the strongest impacts on measuring PDCwith≥1, PDCwm, and DPPR, with small differences in sample size. Instead of the estimates of adherence from PDCwm, those of PDCwith≥1 and DPPR were similar. Furthermore, a tendency toward a higher medication adherence was observed with a smaller study population. Conclusion: The decisions regarding identifying an end-date-of-study and overlaps showed meaningful impacts of all three measures including PDCwith≥1, PDCwm, and DPPR on measuring medication adherence.
Keywords: Daily polypharmacy possession ratio; DPPR; Medication adherence; PDC; Pharmacoepidemiology; Proportion of days covered; Sensitivity analysis